A morphological, anatomical and palynological investigation on Delphinium cilicicumP.H. Davis & Kit Tanand D. petrodavisianum Ilarslan & Kit Tan (Bangladesh Journal of Plant Taxonomy, 2023)
In the present study, the morphological, anatomical and palynological properties of endemic species Delphinium cilicicum P.H. Davis & Kit Tan and D. petrodavisianum İlarslan & Kit Tan belonging tothe genus Delphinium L., Ranunculaceae of Turkey were investigated. D. cilicicum and D. petrodavisianum are very similar morphologically. However, in our studies, it has been determined that there are some differences between the two species in terms of morphological, anatomical and palynological aspects. Based on the data obtained, the similarities and differences between two species were revealed. The cross-sections taken from the roots of two species have peridermis, cortex, vascular tissue and central region, in cross sections taken from the stem have epidermis, cortex, vascular bundle, and pith. In cross sections taken from the sepal and petal have lower and upper epidermis, parenchyma cells and tracheal cells. Through cross-sections of fruit, it was observed that there were two seeds in the fruit and the fruit wall was determined in two species. In palynological research, pollen size, P/E ratio, colpus size, intine-exine thicknesses, amb diameter and distance between colpus were measured. It was revealed that D. cilicicum and D. petrodavisianum had tricolpate, oblate-spheroidal pollen grains.The results obtained from the pollen grains were similar to each other in examined species. The fruits and seeds of two species were examined using SEM microscopy. Micromorphological differences and similarities were determined. The fruits of the species are follicle and globose. The seeds are yellowish brown, sub pyramidal and fine-grained ornamented.Bangladesh J. Plant Taxon. 30(1): 77-88, 2023 (June)